PERBANDINGAN PENGISIAN KAPASITOR OLEH PIEZOELEKTRIK DENGAN BATERI - R. Gustav Rinaldi; Muhammad Anton Kuncoro; Yesiana Arimurti (Universitas Sebelas Maret, 2018)
Abstract: This study aims to compare the charging of capacitors by piezoelectric with batteries. The research method is tapping a 2.7 cm diameter piezoelectric using a finger with a frequency of 30 bpm, 60 bpm, 90 bpm, 120 bpm, 150 bpm and 180 bpm to fill a capacitor of 47 uF which is observed every 10 seconds for 90 seconds. The 30, 60, 90, 120, 150, and 180 bpm beats respectively produced the capacitor end voltage of 575 mV, 882 mV, 980 mV, 1337 mV, 1383 mV, and 1444 mV. After that, the relationship between the beat frequency and the final voltage of the capacitor is analyzed to be compared with charging the capacitor by the battery.Abstrak: Penelitian ini bertujuan untuk membandingkan pengisian kapasitor oleh piezoelektrik dengan baterai. Metode peneltian berupa mengetuk sebuah piezoelektrik berdiameter 2,7 cm menggunakan jari tangan dengan frekuensi 30 bpm, 60 bpm, 90 bpm, 120 bpm, 150 bpm, dan 180 bpm untuk mengisi kapasitor sebesar 47 uF yang tegangannya diamati setiap 10 detik selama 90 detik. Ketukan 30, 60, 90, 120, 150, dan 180 bpm secara berturut – turut menghasilkan tegangan akhir kapasitor sebesar 575 mV, 882 mV, 980 mV, 1337 mV, 1383 mV, dan 1444 mV. Setelah itu, hubungan antara frekuensi ketukan dan tegangan akhir kapasitor dianalsisis untuk dibandingkan dengan pengisian kapasitor oleh baterai.